Trends in the Treatment of Metastatic Colon and Rectal Cancer in Elderly Patients. Issue 5 (May 2016) - Bradley, Cathy J.; Yabroff, K. Robin; Warren, Joan L.; Zeruto, Christopher; Chawla, Neetu; Lamont, Elizabeth B.
Abstract : Background: Little is known about the use and costs of antineoplastic regimens for elderly patients with metastatic colorectal cancer (mCRC). We report population-based trends over a 10-year period in the treatment, survival, and costs in mCRC patients, stratified by ages 65–74 and 75+. Methods: We used Surveillance, Epidemiology, and End Results–Medicare data for persons diagnosed with metastatic colon (N=16117) or rectal cancer (N=4008) between 2000 and 2009. We estimated the adjusted percent of patients who received antineoplastic agents, by type, number, and their costs 12 months following diagnosis. We report the percent of patients who received 3 or more of commonly prescribed agents and estimate survival for the 24-month period following diagnosis by age and treatment. Results: The percentage that received 3 or more agents increased from 3% to 73% in colon patients aged 65–74 and from 2% to 53% in patients 75+. Similar increases were observed in rectal patients. Average 1-year costs per patient in 2009 were 106, 461 and 102, 680 for colon and rectal cancers, respectively, reflecting an increase of 32% and 20%, for patients who received antineoplastic agents. Median survival increased by about 6 and 10 months, respectively, for colon and rectal patients aged 65–74 who received antineoplastic agents, but an improvement of only 1 month of median survival was observed for patients 75+. Conclusions: Expensive multiple agent regimens are increasingly used in older mCRC patients. For patients aged 64–75 years, these treatments may be associated with several months of additional life, but patients aged 75+ may incur considerable expense without any survival benefit. Abstract : Supplemental Digital Content is available in the text.